Proposal for an analog Schwarzschild black hole in condensates of light - Liao, L.; Van Der Wurff, E. C.I.; Van Oosten, D.; Stoof, H. T.C. (American Physical Society, 2019)
By etching a hole in the mirrors or by placing a scatterer in the center of a cavity, we can create a sink for light. In a Bose-Einstein condensate of photons this sink results in the creation of a so-called radial vortex, which is a two-dimensional analog of a Schwarzschild black hole. We theoretically investigate the Hawking radiation and the associated graybody factor of this Schwarzschild black hole. In particular, we determine the density-density and velocity-velocity correlation functions of the Hawking radiation, which can be measured by observing the spatial correlations in the fluctuations in the light emitted by the cavity.
Keywords: Atomic and Molecular Physics, and Optics